Memoria técnica para la zona Cepure de el Centro de Procesos e Innovación para la Industria Sostenible (CEPIIS). (2024)
The absorption plant of the process and innovation center for sustainable industry (CEPIIS) is of great academic and economic value for the University of America, which is why a technical report was generated to ensure its correct operation and the safety of users. providing a prior visualization of the process in a graphical user interface The technical report contains 4 items, First: Instrumentation and piping plans (P&ID) of the real equipment in the plant. Second: Status tables and sequential function graphs for the assigned process. Third: Graphical user interface. And fourth: Safe operation parameters. A verification was carried out of the plans and operation manuals delivered by the manufacturer, which presented inconsistencies in their content, several instruments and some pipes did not coincide with the plans delivered by the manufacturer, in addition to the absence of nomenclatures in the pipe lines. The plans were made that correspond to the real equipment in the plant, with its respective nomenclature and open control loops.